2023
DOI: 10.3390/nu15051143
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Egg Supplement Advances Growing Child’s Growth and Gut Microbiota

Abstract: Protein-energy malnutrition still impacts children’s growth and development. We investigated the prolonged effects of egg supplementation on growth and microbiota in primary school children. For this study, 8–14-year-old students (51.5% F) in six rural schools in Thailand were randomly assigned into three groups: (1) whole egg (WE), consuming 10 additional eggs/week (n = 238) (n = 238); (2) protein substitute (PS), consuming yolk-free egg substitutes equivalent to 10 eggs/week (n = 200); and (3) control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Interestingly, the Yolk-AKD group, which consumed more than 3 eggs/day, showed a tendency for increased HDL-C without affecting TC levels. This is consistent with a previous study in adults who supplemented with 1 egg/ day for 12 weeks [34] and in school-age children who supplemented with 3 eggs/day for 35 weeks [35]. It implies that egg can be a part of healthy KD as long as the diet contains is low in saturated fat and follow a good overall dietary pattern in addition to egg intake [36].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the Yolk-AKD group, which consumed more than 3 eggs/day, showed a tendency for increased HDL-C without affecting TC levels. This is consistent with a previous study in adults who supplemented with 1 egg/ day for 12 weeks [34] and in school-age children who supplemented with 3 eggs/day for 35 weeks [35]. It implies that egg can be a part of healthy KD as long as the diet contains is low in saturated fat and follow a good overall dietary pattern in addition to egg intake [36].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, total dietary energy intake was not reported in all studies and thus the lack of an effect of egg supplementation in some studies may have been masked by an overall dietary energy deficit and negative energy balance. Lastly, a limitation of our statistical analysis was that the control group in two studies (21,22) was counted twice-once in comparison with the one-egg group, and once in comparison with the two-eggs group.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of the 9 interventions demonstrated that children in the egg supplementation groups had a greater increase in weight when compared to those in the control groups by 0.07 kg (95% CI: 0.01, 0.13 kg, p = 0.006; Figure 6). Three comparisons (21,22,25) were in favor of the control group, but results were not statistically significant (Figure 6). There was moderate heterogeneity across interventions (p = 0.02; I 2 = 57.0%).…”
Section: Effect Of Egg Consumption On Change In Body Weightmentioning
confidence: 92%
See 2 more Smart Citations